Analisis Data Pengangguran Terbuka di Kota Medan Tahun 2019-2020 - Windi Jihan Nabila; Zuhrinal M. Nawawi (LPPM IAI Nasional Laa Roiba Bogor, 2023)
This study aims to describe the material for open unemployment in the city of Medan in 2019-2020.Open unemployment is a situation where the person does not work at all and does not try to find work. The study used a qualitative descriptive research method. Unification method collection method uses document study techniques. Data processing using the Spradley Model Analysis method. The results showed that there was an increasing trend of the open unemployment rate in Medan City in the 2019-2020 period of 2.21%. This is caused by several factors, including: economic growth and the Covid-19 pandemic. Keywords: open unemployment, Medan